Celebrating Al and Rose Watkins' 40th Wedding Anniversary - Watkins, Howard::::::::: (1983)
Albert Watkins holding bumper sticker "For the Girl Who Has Everything: HERE I AM" Friend Jennifer Bailey in background; 207 Geneva Ave. #B